2020
DOI: 10.21203/rs.3.rs-104699/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kuwanons, Promising inhibitors against the ACE-2, main protease of SARS-CoV-2 and falcipan-2 using molecular docking

Abstract: In the present scenario, the COVID-19 has affected the nations throughout the world. Till date, neither a vaccine nor a potential medicine is available for the cure from SARS-CoV-2 infection. Main protease of SARS-CoV-2 is responsible for the replication and transcription. Further, this virus binds to the angiotensin converting enzyme-2 (ACE-2) so there is need to find molecule, to avoid the binding of novel virus to ACE-2. It is reported that the molecules binds to falcipan-2 can help in the reduction of infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We then investigated the binding affinity of KC for the spike S1 RBD and the ACE2 receptor using the BLItz system, and found that KC had equilibrium dissociation constants ( K D ) of 5.03 × 10 −4 M for the spike S1 RBD and 8.11 × 10 −4 M for the ACE2 receptor ( Figure 2 and Table 1 ). Collectively, most of the natural product-derived inhibitors targeting the spike S1 RBD:ACE2 receptor interaction have been investigated based on in silico simulation [ 29 , 39 , 40 , 41 , 42 , 43 ]; however, this study not only provides information on a building block of COVID-19 therapeutic agents with the MoA that inhibits SARS-CoV-2 cell entry based on the actual molecular interaction between KC and the spike S1 RBD/ACE2 receptor, it also suggests that further structural analysis of KC derivatives is warranted to obtain increased binding affinity for both proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We then investigated the binding affinity of KC for the spike S1 RBD and the ACE2 receptor using the BLItz system, and found that KC had equilibrium dissociation constants ( K D ) of 5.03 × 10 −4 M for the spike S1 RBD and 8.11 × 10 −4 M for the ACE2 receptor ( Figure 2 and Table 1 ). Collectively, most of the natural product-derived inhibitors targeting the spike S1 RBD:ACE2 receptor interaction have been investigated based on in silico simulation [ 29 , 39 , 40 , 41 , 42 , 43 ]; however, this study not only provides information on a building block of COVID-19 therapeutic agents with the MoA that inhibits SARS-CoV-2 cell entry based on the actual molecular interaction between KC and the spike S1 RBD/ACE2 receptor, it also suggests that further structural analysis of KC derivatives is warranted to obtain increased binding affinity for both proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed the binding energy of KC for the ACE2 receptor, the main protease of SARS-CoV-2, and falcipan-2; however, comprehensive research on the molecular interactions of KC is required [ 29 ]. Thus, we predicted the binding mode of KC to both the spike protein and ACE2 receptor using in silico binding simulation, as well as the molecular interactions between KC and amino acid residues of each protein in that mode using pharmacophore analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations